a laser-engraved wearable sensor for sensitive detection of uric acid and tyrosine in sweat - Yang, Y.; Y. Song; X Bo; J Min; Pak, O.; Zhu, L.; M. Wang; Tu, J.; Kogan, A.; H. Zhang; Hsiai, T.; Z. Li; et al. (Nature Biotechnology, 2019)
Wearable sweat sensors have the potential to provide continuous measurements of useful biomarkers. However, current sensors cannot accurately detect low analyte concentrations, lack multimodal sensing or are difficult to fabricate at large scale. We report an entirely laser-engraved sensor for simultaneous sweat sampling, chemical sensing and vital-sign monitoring. We demonstrate continuous detection of temperature, respiration rate and low concentrations of uric acid and tyrosine, analytes associated with diseases such as gout and metabolic disorders. We test the performance of the device in both physically trained and untrained subjects under exercise and after a protein-rich diet. We also evaluate its utility for gout monitoring in patients and healthy controls through a purine-rich meal challenge. Levels of uric acid in sweat were higher in patients with gout than in healthy individuals, and a similar trend was observed in serum.